2002
DOI: 10.1089/152460902760360559
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and Molecular Mechanisms for Sex Differences in Pharmacokinetics, Pharmacodynamics, and Pharmacogenetics: Part I

Abstract: There are pharmacological differences between women and men that have important clinical consequences. For several drugs, there is a higher incidence in women of drug-induced QT prolongation and a potentially fatal arrhythmia, torsades de pointes. This may be a reflection of the longer baseline QT interval in women. A difference in cardiovascular disease between women and men is that women have a higher mortality rate after myocardial infarction (MI). Women also have a higher rate of hemorrhagic stroke after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 98 publications
2
32
0
Order By: Relevance
“…We checked the distribution of clinical features among males and females, and found that more males were diagnosed at stages III and IV (48.8% in males vs. 42.6% in females), with B-symptoms (46.7% in males vs. 39.5% in females) and died from HIV/AIDS (2.4% in males vs. 0.1% in females), which may partially explain the gender disparity. In addition, this gender disparity may also suggest different genetic, hormonal, and metabolic influences on treatment response [20][21][22], or different stress that patients bear and release [23]. Another possible explanation is that some etiological risk factors more frequently observed among males may also have a negative effect on their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…We checked the distribution of clinical features among males and females, and found that more males were diagnosed at stages III and IV (48.8% in males vs. 42.6% in females), with B-symptoms (46.7% in males vs. 39.5% in females) and died from HIV/AIDS (2.4% in males vs. 0.1% in females), which may partially explain the gender disparity. In addition, this gender disparity may also suggest different genetic, hormonal, and metabolic influences on treatment response [20][21][22], or different stress that patients bear and release [23]. Another possible explanation is that some etiological risk factors more frequently observed among males may also have a negative effect on their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex differences in gastric emptying, acidity, and enzymes, in the activity of several isoenzymes in the liver, and in the glomerular filtration rate have been reported. 19 Whether the traditional risk factors are less potent in women (perhaps based on a protective effect of estrogen) or whether women have more diffuse coronary atherosclerosis to account for the observation that despite a higher prevalence of traditional risk factors in women undergoing coronary revascularization, the extent of epicardial disease detected by angiography is similar to that seen in men is unclear. However, these findings have lead to the evaluation of other potential risk factors or markers of disease in women.…”
Section: Sex-related Differences In the Biology And Pathophysiology Omentioning
confidence: 99%
“…4. Pharmacologic dosing adjustment in consideration of issues of aging, 63 gender, 64 ethnicity, and comorbidities, for example, renal disease and liver disease and ethnicity. Aggressive preventive cardiovascular regimens are optimally tolerated when body weight-and renal functionadjusted, including the elderly, women, and smaller-sized men.…”
Section: Use Of Multiple Drug Combinations (Coexistent Conditionsmentioning
confidence: 99%